Monitoring of Caffeine Consumption Effect on Skin Blood Properties by Diffuse Reflectance Spectroscopy - Milanic, M; Hren, R; Stergar, J; Simoncic, U (Physiological research, 2024)
Caffeine is the most widely consumed psychoactive substance worldwide, affecting numerous tissues and organs, with notable impacts on the central nervous system, heart, and blood vessels. The effect of caffeine on vascular smooth muscle cells is an initial transient contraction followed by significant vasodilatation. In this study we investigate the use of diffuse reflectance spectroscopy (DRS) for monitoring of vascular changes in human skin induced by caffeine consumption. DRS spectra were recorded on volar sides of the forearms of eight healthy volunteers at time intervals of 0, 30, 60, 120, and 180 min after consumption of caffeine, while one subject served as a negative control. Analytical diffusion approximation solutions for diffuse reflectance from three-layer structures were used to assess skin composition (e.g. dermal blood volume fraction and oxygen saturation) by fitting these solutions to experimental data. The results demonstrate that cutaneous vasodynamics induced by caffeine consumption can be monitored by DRS, while changes in the control subject not consuming caffeine were insignificant.
Keywords: Caffeine; lidé; kofein; spektrální analýza; Skin; kůže; Spectrum Analysis; Humans